PELATIHAN PENGGUNAAN MENDELEY SEBAGAI SOFTWARE MANAJEMAN REFERENSI UNTUK PENULISAN TUGAS AKHIR - Fitri Aida Sari (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
Final Project Writing is the obligation of every student to be able to complete his studies. In the process of preparing the Final Project, one of the important things that need to be learned by students is how to arrange references properly. Currently, there are many applications that can help in the reference management process, one of these applications is Mendeley. The purpose of this community service activity is to provide students with an understanding of how to use the Mendeley application so that there is an increase in the quality of scientific work, especially the Final Project that students will work on. The methods used in this Mendeley training include lectures, practice, discussions and online questions and answers through the Google Meet application. Participants in this Mendeley training were students of the Civil Engineering Study Program, University of Banten Jaya with 10 participants. The results of the training activities showed an increase in students' knowledge and understanding in using the Mendeley application. All students who take part in the training can install Mendeley on their respective laptops, enter documents that are used as reference sources into the Mendeley application, do citations and create a bibliography using the menu found on Mendeley.